2017
DOI: 10.3389/fcimb.2017.00279
|View full text |Cite
|
Sign up to set email alerts
|

A Genetically Modified attenuated Listeria Vaccine Expressing HPV16 E7 Kill Tumor Cells in Direct and Antigen-Specific Manner

Abstract: Attenuated Listeria monocytogenes (L. monocytogenes, LM) induces specific CD8+ and CD4+ T cell responses, and has been identified as a promising cancer vaccine vector. Cervical cancer is the third most common cancer in women worldwide, with human papillomavirus (HPV), particularly type 16, being the main etiological factor. The therapeutic HPV vaccines are urgently needed. The E7 protein of HPV is necessary for maintaining malignancy in tumor cells. Here, a genetically modified attenuated LM expressing HPV16 E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…stress, microbiota diversity, variation in vaccination dose) may cause this variability and need to be further evaluated. Most studies showed Lm-induced immunity against foreign antigens including tumor associated antigens, HIV-1 gag, Mycobacterium tuberculosis and Aeromonas hydrophila ( Friedman et al., 2000 ; Jia et al., 2017 ; Yin et al., 2017 ; Flickinger et al., 2018 ; Kim et al., 2019 ; Zeng et al., 2020 ), and they focused on the cellular immune response. One of the few studies that investigated both cellular and humoral immunity ( Mahdy et al., 2019 ) observed rising antibody titers 14 days after the first vaccination with 1 x 10 6 bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…stress, microbiota diversity, variation in vaccination dose) may cause this variability and need to be further evaluated. Most studies showed Lm-induced immunity against foreign antigens including tumor associated antigens, HIV-1 gag, Mycobacterium tuberculosis and Aeromonas hydrophila ( Friedman et al., 2000 ; Jia et al., 2017 ; Yin et al., 2017 ; Flickinger et al., 2018 ; Kim et al., 2019 ; Zeng et al., 2020 ), and they focused on the cellular immune response. One of the few studies that investigated both cellular and humoral immunity ( Mahdy et al., 2019 ) observed rising antibody titers 14 days after the first vaccination with 1 x 10 6 bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies have showed that the antitumor mechanism of listeria-based therapeutic vaccines might be related to the reduced percentage of Tregs and CD8 + T cell infiltration in the tumor microenvironment 37 , 38 . Tregs have an adverse effect on antitumor immunity in many tumors 39 , including cervical cancer 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Tregs have an adverse effect on antitumor immunity in many tumors 39 , including cervical cancer 40 . CD8 + T cells may participate in specific antitumor immune responses at tumor local sites 38 . Therefore, we detected the number of Tregs and CD8 + T cells from TILs in different treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…LM has been shown to have an exceptional capacity to induce anti-tumor immunity to tumor-associated antigens, such as HPV16 E7 (Jia et al, 2017), influenza virus NP3 (Pan et al, 1999), HIV-1 gag (Okuda et al, 1995;Jiang et al, 2007), tuberculosis , metastatic pancreatic cancer (Le et al, 2016), and canine osteosarcoma (Mason et al, 2016). In this study, an AH vaccine using attenuated LM as delivery vector was described, and the safety and the immunogenicity of the vaccine were assessed.…”
Section: Discussionmentioning
confidence: 99%